Socio-Economic Atlas of Myanmar - Kraas, Frauke (Franz Steiner Verlag, 2017)
The Socio-Economic Atlas of Myanmar focuses on the analysis and evaluation of regional differences in geographical conditions, natural resources, infrastructure and, in particular, the socio-economic development in the states and regions of the country in the current transformation process of Myanmar. The Atlas is based on international literature, statistical data, qualitative research and spatial information in a Geographic Information System on Myanmar. The spatial analyses aim to increase the state of knowledge about Myanmar both within the country and abroad, and to support decision-making on spatial development policy.